The evolution of Crema (Cream) wares in the Valley of Oaxaca – Insights from INAA and ceramic petrography. (June 2022) - Minc, Leah; Winter, Marcus; Martínez López, Cira
Highlights: We combine INAA and ceramic petrography to examine variability in crema wares ca . 700 BCE – 850 CE. Chemical and mineral analyses indicate four different areas in the northern valley produced cremas . Production locations and type of vessels produced (utilitarian vs. elite wares) shifted over time. These new results challenge long-standing assumptions regarding the significance of crema vessels. Abstract: The visually distinctive pastes of crema (cream) ceramics hold a special place in reconstructing the prehistory of highland Oaxaca, Mexico. Their characteristic large, white, angular (crystalline) inclusions have been linked to a single clay source located just north of Monte Albán, thus the ware is often interpreted as a marker of contact with Monte Albán. To assess this assumption of a single, localized production area, we analyze a large sample of crema ceramics from the Valley of Oaxaca ranging in date from ca . 700 BCE to 850 CE. Specifically, we combine both INAA (N = 754) and ceramic petrography (N = 27) to examine the internal consistency of crema wares and address the question of whether all cremas share the same chemical and mineralogical signature indicating a common provenance, or whether chemical and mineral subgroups reflect different manufacturing locales for this important ware. Our results indicate that cremas have a longer and more complex history than previously thought, and potentially affect how we employ this ceramic ware to understand the influence of Monte Albán within the valley and beyond.